Prediksi Hiperlaktatemia Terhadap Sepsis Dan Luaran Buruk Pada Pasien Intracerebral Hemorrhage - Supardi; Retnaningsih; Dodik Tugasworo; Ageng Priatmaja (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2026)
Introduction: Sepsis is a serious complication and major cause of mortality among intracerebral hemorrhage (ICH) patients in the intensive care unit (ICU). Serum lactate is commonly used as a prognostic biochemical marker for sepsis in critically ill patients. Aims: This study aimed to evaluate the relationship between serum lactate levels, sepsis incidence, and clinical outcomes in ICH patients in ICU of Dr. Kariadi Hospital. Methods: A retrospective observational cohort study was performed on 30 ICH patients hospitalized in the ICU during 2024. Data normality tested using Shapiro-Wilk; non-normal data were analysed by Mann-Whitney U, categorical data by Chi-square test. Results: Among 30 patients (12 males, 18 females), 20 had hyperlactatemia (>2 mmol/L). The hyperlactatemia group had higher sepsis incidence (90% vs. 50%, p=0.014), MODS (70% vs. 30%, p=0.037), high NLR (>8; 80% vs. 40%, p=0.028), longer ventilator (>8 days; 75% vs. 40%, p=0.007), and LOS (>8 days; 75% vs. 40%, p=0.007). Discussion: Routine serum lactate monitoring in ICH ICU patients is recommended for early detection and prognosis of sepsis. Larger prospective studies are needed to validate these findings. Keywords: ICU, intracerebral haemorrhage, lactate, prognosis, sepsis